Clinical Presentation and Outcomes of Hospitalized Patients with Chronic Kidney Disease and COVID-19 Variant Omicron - Wang X; Cao X; Liang S; Cai G (Dove Medical Press, 2024)
Xiaolong Wang, Xueying Cao, Shuang Liang, Guangyan Cai Department of Nephrology, First Medical Center of Chinese PLA General Hospital, Chinese PLA Institute of Nephrology, State Key Laboratory of Kidney Diseases, National Clinical Research Center for Kidney Diseases, Beijing Key Laboratory of Kidney Diseases, Beijing, People's Republic of ChinaCorrespondence: Xueying Cao, Department of Nephrology, Chinese PLA General Hospital, Chinese PLA Institute of Nephrology, State Key Laboratory of Kidney Diseases, National Clinical Research Center for Kidney Diseases, 28 Fuxing Road, Beijing, 100853, People's Republic of China, Tel +86 159 1049 3688, Email 450391715@qq.com; 18911622536@163.comPurpose: To investigate the clinical characteristics of hospitalized patients with chronic kidney disease (CKD) and novel coronavirus (SARS-CoV-2) infection and identify potential risk factors that contribute to mortality.Patients and Methods: This is a retrospective study, conducted on patients with CKD who were admitted to the First Medical Center of the People's Liberation Army General Hospital between December 1, 2022, and February 28, 2023. All patients were also infected with SARS-CoV-2. We analyzed the clinical characteristics of patients, and the patients were categorized into a survival group and a death group whose characteristics were compared. Cox regression analysis was used to identify risk factors that affected patient prognosis.Results: A total of 406 patients were enrolled in this study, including 298 males (73.4%). The average age was 80.5 (67.0, 88.0) years, and the patients had an average estimated glomerular filtration rate (eGFR) of 50.3 (25.0- 79.0) mL/min/1.73m². A total of 158 individuals died during hospitalization, resulting in a mortality rate of 38.9%. Renal function was worse in the death group than in the survival group (P < 0.001). Patients in the death group had more severe COVID-19 disease and higher CKD staging than those in the survival group (all P values < 0.001). Multivariate Cox regression analysis identified several risk factors that affected patient mortality, including being male, a higher resting heart rate (RHR) upon admission, dyspnea, a low lymphocyte count (Lym), a high international standardized ratio (INR), a high Acute Physiology and Chronic Health Evaluation II (APACHE II) score, heart failure, and the need for mechanical ventilation during the disease.Conclusion: Hospitalized patients with CKD who were infected with SARS-CoV-2 (38.9%) had a relatively high mortality rate (38.9%). Furthermore, a marked correlation was observed between a reduced eGFR and an increased risk of mortality.Keywords: SARS-CoV-2, estimated glomerular filtration rate, respiratory failure, mortality rate